PERBANDINGAN TINGKAT KECEMASAN PERAWAT DALAM PENANGANAN PASIEN COVID-19 DI UNIT GAWAT DARURAT, ISOLASI WINGS, DAN ISOLASI UTAMA - Kadek Febri Dwi Upayanti; Komang Menik Sri Krisnawati; Ni Putu Emy Darma Yanti (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2021)
Coronavirus Diseases 2019 (Covid-19) is a major health problem in the world nowadays. Covid-19 has negative impacts on the nurse’s mental health, one of them is anxiety. Continuous exposure of anxiety has negative impacts on the physical, psychological, and work performance of nurses. This study aimed to nurses’ anxiety levels in handling Covid-19 patients at Emergency Room, Wings Isolation, and Main Isolation in Bangli General Hospital. This study was a quantitative study with comparative analytical study. This research used a cross-sectional study design. The sample size in this study was 43 nurse selected using random sampling technique. The instrument that used in this study was ZSAR- S (Zung Self Anxiety Rating-Scale). The Kruskal Wallis comparative test showed a significant result on the level of anxiety variable with p-value = 0.009 (p <0.05), which means there differences of nurses anxiety level at Emergency Room, Wings Isolation, and Main Isolation. The results also showed that 31.25% of nurses in the Wings Isolation Room experienced mild anxiety. In conclusion, nurses who work in the Wings Isolation Room experienced higher anxiety compared to nurses who work in the Emergency Room and Main Isolation Room.